Osteoarthritis Patients’ Experiences of Pharmacotherapy for Pain Management in Iran: A Qualitative Study - Zamanzadeh, Vahid; Ahmadi, Fazlollah; Behshid, Mozhgan; Irajpoor, Alireza; Zakeri-Milani, Parvin (Drug Research, 2017)
Despite the effectiveness of pharmacotherapy for pain management in patients with osteoarthritis (OA), personal biases in the selection, administration, and continuation of pharmacotherapy challenge the proper management of symptoms and the effectiveness of the therapy. This study was conducted to carry out an in-depth examination of the experiences of patients with OA about their use of pharmacotherapy for the OA pain management and the existing challenges. The present qualitative study was conducted on 17 patients with OA, 5 of their family members and 8 healthcare personnel using a conventional content analysis approach. Data were collected through 35 interviews, which were unstructured at first but became semi-structured later on. Data collection continued until data saturation and analyzed simultaneously. The criteria used to determine the rigor of the study included the credibility, transferability, dependability and conformability of the data. The analysis of the data revealed 3 main categories and 8 subcategories. The main categories including preference for non-pharmacological modalities, preference for symptomatic slow-acting drugs for osteoarthritis (SySADOAs) and preference for vitamins and minerals. Briefing the patients on the therapeutic goals, participating them in the clinical decision-making process, modifying drug administration patterns through prescribing the minimum effective dosage and substituting alternative therapies whenever possible, consistently monitoring the therapeutic responses and any unexpected complications and use of complementary treatments, makes up strategies that can help improve OA pain management.
Keywords: Osteoarthritis; behavioural pharmacology; analgesic drugs; anti-inflammatory drugs; adverse drug reactions